Antiresorptive and anti-angiogenetic octacalcium phosphate functionalized with bisphosphonates: An in vitro tri-culture study. (May 2017) - Forte, Lucia; Torricelli, Paola; Boanini, Elisa; Gazzano, Massimo; Fini, Milena; Bigi, Adriana
Graphical abstract: Abstract: Development of new materials for the local administration of bisphosphonates (BPs) is aimed to avoid the negative side effects of prolonged systemic use of these potent drugs. In this work, we synthesized octacalcium phosphate (OCP) in the presence of two potent BPs and obtained a single crystalline phase up to a zoledronate and alendronate content of 3.5 wt% and 5.2 wt%, respectively. Both BPs provoke minor structural modifications and a reduction of the crystal dimensions of OCP, which suggests a preferential interaction of the BPs with the structure of the calcium phosphate. Alendronate containing samples display increased values of zeta potential with respect to that of OCP, and an initial burst release of the BP in solution. At variance, the zeta potential of zoledronate functionalized samples decreases on increasing the content of zoledronate, which is not appreciably released in solution. Bone microenvironment response to the composite materials was investigated in vitro using a triculture model. BP functionalized samples downregulate the viability of the cells, sustain osteoblast differentiation and accelerate the production of collagen type I and osteocalcin. At variance, they inhibit monocyte differentiation into osteoclast and provoke a dose dependent reduction of VEGF production, exhibiting antiresorptive and anti-angiogenetic properties that can be usefully exploited for the local treatment of abnormal bone losses. Statement of Significance: Bisphosphonates (BPs) are powerful drugs for the treatment of bone diseases. However, BPs systemic administration suffers several undesirable side effects, which stimulate the development of suitable systems for their local administration. In this study we functionalized octacalcium phosphate (OCP) with alendronate and zoledronate in order to get biomaterials able to couple the good biological performance of OCP with the therapeutic properties of the BPs. The results provide novel information on the interaction between these two potent BPs and octacalcium phosphate. Moreover, the triculture in vitro study indicates that the synthesized composite materials stimulate the production of bone extracellular matrix, inhibit monocytes differentiation into osteoclasts and downregulate the release of Vascular Endothelial Growth Factor (VEGF) in a dose dependent way. The data allow to state that the new composite materials can be usefully employed for the local treatment of diseases involving abnormally high bone resorption.